Novel patterning of flexible and transparent Ag nanowire electrodes using oxygen plasma treatment - Kim,H; Lee,G; Becker,S; Kim,J; Kim,H; Hwang,B (Journal of Materials Chemistry C, 2018)
We report a novel patterning method using oxygen plasma treatment for flexible and transparent Ag nanowire electrodes. Using a dry film photoresist as a solid-state film-type photoresist, Ag nanowires were selectively oxidized under oxygen plasma treatment. Microstructural analysis revealed that the Ag nanowires were fully oxidized after 30 s of oxygen plasma treatment, which was also reflected in the changes in the optoelectronic properties of the Ag nanowires. The fully oxidized Ag nanowires could be completely dissolved in NH3 solution (aq.), without using a toxic etchant to form sharp patterns of Ag nanowire electrodes. To further confirm the applicability of the patterning technique demonstrated here in electronic devices, MoS2 thin-film transistors (TFTs) with patterned Ag-nanowire source/drain (S/D) electrodes were fabricated and they showed similar performances to typical MoS2 TFTs with thin-film-type Ti/Au S/D electrodes.